Multivariate analysis of some circular economy indicators - Fernanda Figueiredo; Adelaide Figueiredo (Research in Statistics)
This data-based study aims to understand the progress made by EU countries in recent years on key areas of the circular economy by analyzing some indicators. The data have been collected from the Eurostat database over the period 2013-2021. After a preliminary analysis of the data set, a double principal component analysis has been used. This approach provides insights into the evolution of the countries and correlations between the indicators, highlighting which EU countries are the most (or least) similar to each other. The findings of this study indicate that EU countries collectively have advanced towards a circular economy in various indicators, with certain countries showing more notable progress than others. Some countries are even considered outliers, for positive or negative reasons, in some of the indicators. Overall, the Western EU countries perform better than the Eastern countries on most of the indicators analyzed, especially for resource productivity, municipal waste management, circularity rate, private investment in the circular economy sectors, and gross added value in circular economy sectors. The exceptions are for the generation of municipal waste, percentage of persons employed in circular economy sectors, and greenhouse gas emissions, the ones where the Eastern countries in general perform better.